Answer:
-3c
Step-by-step explanation:
The given expression is:
[tex]\frac{\frac{6c^{2}+3c}{-4c+2}}{\frac{2c+1}{4c-2}}[/tex]
We need to simplify this expression. The rational expression in the denominator can be multiplied to numerator by taking its reciprocal as shown below:
[tex]\frac{\frac{6c^{2}+3c}{-4c+2}}{\frac{2c+1}{4c-2}} \\\\ =\frac{6c^{2}+3c}{-4c+2} \times \frac{4c-2}{2c+1}\\\\=\frac{3c(2c+1)}{-(4c-2)} \times \frac{4c-2}{2c+1}\\\\ =-3c[/tex]
Thus, the given expression in simplified form is equal to -3c
Answer:
-3c
Step-by-step explanation:
We are given that an expression
[tex]\frac{\frac{6c^2+3c}{-4c+2}}{\frac{2c+1}{4c-2}}[/tex]
We have to find an expression which is equal to given expression
Taking common 3c from nominator and -2 from denominator in dividened and 2 common in divisor then we get
[tex]\frac{\frac{3c(2c+1)}{-2(c-2)}}{\frac{2c+1}{2(2c-1)}}[/tex]
[tex]\frac{3c(2c+1)}{-2(2c-1)}\times \frac{2(2c-1)}{(2c+1)}[/tex]
By reciprocal divisor
By canceling same factor
Then ,we get
[tex]\frac{\frac{6c^2+3c}{-4c+2}}{\frac{2c+1}{4c-2}}[/tex]
=-3c
The quotient k and 22 is −66.
Answer: k=−1,452
Step-by-step explanation:
k/22 x 22 = −66 x22
The value of 'k' can be determined by isolating 'k' in the equation. This results in k = 22 * -66, simplifying to k = -1452.
Explanation:The equation conveyed in the question can be written as k/22 = -66. To find the variable k's value, we need to isolate k in the equation. This can be done by keeping the inverse operation on both sides of the equation balanced. Since k is currently divided by 22, we must multiply both sides of the equation by 22 to get k independently.
When we do this, the equation becomes k = 22 * -66. Then, solve for k by multiplying 22 and -66 together. So, k equals -1452.
Learn more about Algebra here:https://brainly.com/question/24875240
#SPJ3
4. Perform the indicated operation on polynomials.
a. (4x2 + 5x - 7) + (2x2 - 7x - 3)
b. (8m - 2n - 4) - (6m - 3n + 2)
c. (30+4) (5c-2)
Answer:
A) 6x2-2x-10
B) 2m+1n-6
C) 170c-68
Step-by-step explanation:
4x2 + 2x2 = 6x2 5x -7x = -2x -7 + -3 = -10
8m - 6m = 2m -2n + 3n = 1n -4 - 2 = -6
34 x 5c = 170 34 x -2 = -68
Answer:
Step-by-step explanation:
a) (4x2 + 5x - 7) + (2x2 - 7x - 3)
This is an addition question. We have to perform addition
The first step is open the parenthesis/brackets.
4x^2+5x-7 + 2x^2 -7x-3
Arrange the terms according to the exponents:
4x^2+2x^2-7x+5x-7-3
Combine the like terms:
6x^2-2x-10
Thus the answer is 6x^2-2x-10
b) (8m - 2n - 4) - (6m - 3n + 2)
We have to perform subtraction:
There is a rule in the subtraction that when you open the brackets then the signs of 2nd bracket will be multiplied by the negative sign:
Open the brackets:
8m - 2n - 4 - 6m+3n-2
Arrange the terms:
8m-6m+3n-2n-4-2
Combine the like terms:
2m+n-6
Thus the answer is 2m+n-6
c) (30+4) (5c-2)
This expression shows the operation of multiplication:
Solve the first parenthesis.
(34)(5c-2)
Now multiply 34 by each term of 2nd bracket:
=170c-68
Thus the answer is 170c-68....
Which of the following is three-dimensional and infinitely large?
Answer:
Option C Geometric space
Step-by-step explanation:
Which of the following is three-dimensional and infinitely large?
Verify each case
case A) A plane is two-dimensional and infinitely large.
case B) A line is infinitely large but is only one-dimensional
case C) Geometric space is three-dimensional and infinitely large
case D) A solid is three-dimensional, but not infinite
therefore
The answer is Geometric space
Answer:
Geometric Space
Step-by-step explanation:
Which of the following is three-dimensional and infinitely large?
Verify each case
case A) A plane is two-dimensional and infinitely large.
case B) A line is infinitely large but is only one-dimensional
case C) Geometric space is three-dimensional and infinitely large
case D) A solid is three-dimensional, but not infinite
therefore
The answer is Geometric space
Jason deposits $5 into his savings account twice a week for 6 weeks. How much money will he have saved after 6 weeks?
Let s stand for the amount of money saved.
Equation:
How much money did he save?
Show your work.
First person who answers gets to be followed and marked brainliest.
Answer:
(5x2)6=60
60
Step-by-step explanation:
Answer:
Let s stand for the amount of money saved.
[tex]2*5(6)=s[/tex]
He saved $60.
[tex]s=2*5(6)=10*6=60[/tex]
Help With the problem! With picture
Answer:
Slope is 20
y-intercept is 50
Step-by-step explanation:
y=mx+b is slope-intercept form where m is the slope and b is the y-intercept where x and y are the variables.
For your equation the slope is 20 and the y-intercept is 50 where m and y are variables.
The y-intercept is what you initially start with and here that is 50. The slope is a rate. So you are getting 20 dollars added per month.
Drag each tile to the correct box.
Calculate the sum of each expression. Arrange the expressions in the order of their value from largest to smallest.
Answer:
6 3/5 , 3 4/5, 4/5
Step-by-step explanation:
1) -8 2/5 + 9 1/5 =
-42/5 + 46/5 = 4/5
2) 9 2/5 + (-5 3/5) =
47/5 + -28/5 = 19/5 = 3 4/5
3). 2 1/5 + 2 2/5 =
11/5 + 22/5 = 33/5 = 6 3/5
answer is tile 3 then tile 2 then tile 1
6 3/5 , 3 4/5, 4/5
The expression are arranged in the descending order, that is from largest to smallest as follows:
33/5 > 19/5 > 4/5
What are expressions?
The expressions are the combination of various constants numbers and mathematical symbols. They form a meaningful context that is in accordance to the mathematical rules and theories.
The expressions are computed as follows:
Given:
-8 2/5 + 9 1/5
Computation:
={(-8*5)+2}/5 + {(-9*5)+1}/5
=-42/5 + 46/5
= 4/5
Given:
9 2/5 + (-5 3/5)
Computation:
={(9*5)+2}/5 + {(-5*5)+3}/5
=47/5 + -28/5
= 19/5
Given:
2 1/5 + 2 2/5
Computation:
={(2*5)+1}/5 + {(2*5)+2}/5
=11/5 + 22/5
= 33/5
Therefore, the expressions will be arranged in the order; largest to smallest: 33/5 > 19/5 > 4/5
Learn more about expressions, here:
https://brainly.com/question/12130720
#SPJ2
HELP ASAP FIND EACH DERIVATIVE..... 7) 3x^2y^2=4x^2-4xy
8) 5x^3 + xy^2= 5x^3y^3
9)y=(3x^4+5x^3-5)/2x^4-4
Answer:
7. (4x - 3xy^2 - 2y) / (3x^2y + 2x).
Step-by-step explanation:
Implicit differentiation:
7. 3x^2 y^2 = 4x^2 - 4xy
6x * y^2 + 3x^2 * 2y y' = 8x - 4(x y' + y)
6xy^2 + 6x^2y y' = 8x - 4x y' - 4y
6x^2y y' + 4x y' = 8x - 6xy^2 - 4y
y' = (8x - 6xy^2- 4y) / (6x^2y + 4x)
y' = 2(4x - 3xy^2- 2y) / 2(3x^2y + 2x)
= (4x - 3xy^2 - 2y) / (3x^2y + 2x).
Numbers 8 and 9 are done in the same way.
We use the Chain, Product and Quotient rules where applicable.
Which is a rational function?
a. y= x-3^x / x^2. b. y= x^2 - x + 4. c. y= x-5/ 2. d. y= 2/x
ANSWER
d.
[tex]y = \frac{2}{x} [/tex]
EXPLANATION
A rational function is of the form:
[tex]r(x) = \frac{p(x)}{q(x)} [/tex]
where p(x) and q(x) are polynomial functions and q(x)≠0.
The first option contains the exponential function
[tex] {3}^{x} [/tex]
This disqualifies it from being a rational function.
The second and third options are polynomial functions.
By definition, all polynomials are rational functions.
The last option is a typical rational function because it has at least an asymptote.
The most correct choice is
[tex]y = \frac{2}{x} [/tex]
Which logarithmic equation has the same solution as x-4=2^3
Answer:
log₁₀ (10¹²)
Step-by-step explanation:
First you should find the solution to the given equation
x-4=2³
x-4=8
x=8+4=12
Now observe the behavior of logarithmic equations with the base 10
log₁₀ 100=2
log₁₀ 10000=4
log₁₀ 1000000=6
To get the answer to
log₁₀ y=12
Then y=10¹².........................how?
check for the first case
log₁₀ 100=2 this can be written as
10²=100
This means to get y in log₁₀y=12 you should rise the base to power 12
y=10¹²
This is to say that
log₁₀ (10¹²) = 12
What is the total surface area of a rectangular prism that is 4 inches deep, 5 inches high, and 15 inches across?
Answer:
The total surface area of a rectangular prism is 310 inches
Step-by-step explanation:
The surface area of rectangular prism can be found using formula
Surface Area = 2(lw+hl+hw)
Where l = length
h = height
w = width
We are given:
l = 4
h = 5
w = 15
Putting values in the formula:
Surface Area = 2(lw+hl+hw)
Surface Area = 2((4*15)+(5*4)+(5*15))
Surface Area = 2(60+20+75)
Surface Area = 2(155)
Surface Area = 310 inches
So, The total surface area of a rectangular prism is 310 inches
Answer:
The total surface area of a rectangular prism is 310 inches
Step-by-step explanation:
The surface area of rectangular prism can be found using formula
Surface Area = 2(lw+hl+hw)
Where l = length
h = height
w = width
We are given:
l = 4
h = 5
w = 15
Putting values in the formula:
Surface Area = 2(lw+hl+hw)
Surface Area = 2((4*15)+(5*4)+(5*15))
Surface Area = 2(60+20+75)
Surface Area = 2(155)
Surface Area = 310 inches
So, The total surface area of a rectangular prism is 310 inches
Colin surveyed his classmates about their favorite subject in school.
Colin’s Survey Results
Favorite Subject
Number of Students
Math
14
Language Arts
7
Earth Science
10
Life Science
11
Which statement is true?
The ratio of science fans to language arts fans is 10:7.
The ratio of language arts fans to science fans is 1:3.
The ratio of math and science fans to language arts fans is 24:7.
The ratio of language arts fans to math and science fans is 5:1.
Answer:
The correct answer is "The ratio of language arts fans to science fans is 1:3. "
Step-by-step explanation:
The ratio is the amount of students with a favorite subject per (compare with) the amount of students that prefer other subject.
We are going to analyze every statement
The ratio of science fans to language arts fans is 10:7. FALSE.Science fans are 21 (Earth Science +Life Science ). This ratio is 21:7 or 3:1.
The ratio of language arts fans to science fans is 1:3. TRUE.This ratio is 7:21, we can divide this numbers so that is the same of 1:3
The ratio of math and science fans to language arts fans is 24:7. FALSE.This ratio is 35:7
The ratio of language arts fans to math and science fans is 5:1. FALSE.This ratio is 7:35 or 1:5
Answer:
b :) hope this doesn't help
Step-by-step explanation:
i mean its the right answer but maby the wrong question you were looking for like what happens to me i put in the questions it goes voo doo magic to brainly i open it and its the wrong question i hate when it does that so then i have to copy and paste the question to put it on here just to find the wrong answer.
A diameter is a line segment whose endpoints are on a circle. It is a special type of chord because it must contain the _____ of the circle HELP!!!!!!!!!!
A diameter is a special type of chord that passes through the center of a circle. It has its endpoints on the circle's circumference, with the center of the circle as its midpoint.
Explanation:In the field of mathematics, a diameter is indeed a special type of chord. The unique characteristic of a diameter, differentiating it from other chords, is that it must contain the center of the circle - that is the definition finds its completion. As a line segment, a diameter has its endpoints on the circumference of the circle and its middle point is the center of the circle. So, when referring to a diameter, you are essentially talking about the largest chord in a circle that passes through the center.
Learn more about Diameter here:https://brainly.com/question/32968193
#SPJ6
Chris lost $5.29 playing poker in one week. If this continued, what would be his net winnings or losses after five weeks ?
Answer:
$26.45
Step-by-step explanation:
If Chris lost $5.29 playing poker in one week, in five weeks he would lose $26.45.
$5.29 lost per week.
5 weeks.
$5.29 x 5 = $26.45.
The net loss of Chris after five weeks will be $26.45.
Average value per week: -$5.29
Net loss after five weeks: -$5.29 x 5 = -$26.45
Verify the identity. 1+tan x/sin x + cos x= sec x
Step-by-step explanation:
Taking left hand side:
[tex]\frac{1+tan\ x}{sin\ x+cos\ x}\\=\frac{1+\frac{sin\ x}{cos\ x} }{sin\ x+cos\ x}\\=\frac{\frac{cos\ x+sin\ x}{cos\ x} }{sin\ x+cos\ x}\\=\frac{cos\ x+sin\ x}{cos\ x} * \frac{1}{sin\ x+cos\ x}\\=\frac{1}{cos\ x}[/tex]
1/cos x is equal to sec x.
So,
[tex]\frac{1}{cos\ x} = sec\ x[/tex]
Hence proved ..
What is the slope and y-intercept of the equation 3(y − 2) + 6(x + 1) − 2 = 0? A. slope = -2, y-intercept = B. slope = 2, y-intercept = C. slope = -2, y-intercept = D. slope = 2, y-intercept = E. slope = -2, y-intercept = Reset Next
Answer:
Step-by-step explanation:
Carrying out the indicated multiplication, we get
3y - 6 + 6x + 6 - 2 = 0.
Combining like terms, we get 3y = -6x + 2.
Solving for y: y = -2x + 2/3.
The slope is -2 and the y-inercept is 2/3.
The slope will be -2 and y-intercept will be 8/3.
Slope and y-intercept are key elements of a linear equation. The slope, denoted by b, describes the steepness of a line, while the y-intercept, denoted by a, is where the line crosses the y-axis.
The equation 3(y - 2) + 6(x + 1) - 2 = 0 can be rewritten as 3y + 6x - 12 + 6 - 2 = 0, which simplifies to 3y + 6x - 8 = 0.
To find the slope-intercept form, we can rearrange the equation to y = -2x + 8/3, where the slope is -2 and the y-intercept is 8/3.
PLEASE HELP ME !! I need it ..
Answer:
D
Step-by-step explanation:
The Rational root theorem states that the possible roots ( zeros) of a polynomial are of the form
( plus or minus ) factors of the constant term divided by the factors of the leading coefficient.
For x³ - 3x² + 27x - 8
The factors of constant term (- 8) are ± 1, 2, 4, 8
The coefficient of the leading term x³ is 1
Hence possible zeros are
± ([tex]\frac{1,2,4,8}{1}[/tex]) = ± 1, ± 2, ± 4, ± 8 → D
Find the distance between the points. (-4, -2) and (5, 2) ^97 2^14 2^5 ^5
Answer:
The distance between 2 points is √97 or 9.84
Step-by-step explanation:
The distance between two points can be found using distance formula:
[tex]d(x_{1},x_{2})=\sqrt{(x_{2}-x_{1})^2+(y_{2}-y_{1})^2}[/tex]
x₁ = -4, y₁ = -2 x₂ =5 and y₂ = 2
Putting values:
[tex]d(x_{1},x_{2})=\sqrt{(5-(-4))^2+(2-(-2))^2}\\d(x_{1},x_{2})=\sqrt{(5+4)^2+(2+2)^2}\\d(x_{1},x_{2})=\sqrt{(9)^2+(4)^2} \\d(x_{1},x_{2})=\sqrt{81+16}\\d(x_{1},x_{2})=\sqrt{97}[/tex]
So, the distance between 2 points is √97 or 9.84
Answer:
=sqrt(97)
Step-by-step explanation:
The distance between the two points is found by
d = sqrt(( x2-x1)^2 + (y2-y1)^2)
= sqrt( ( 5--4)^2 + (2--2)^2)
= sqrt( ( 5+4)^2 + (2+2)^2)
= sqrt( ( 9)^2 + (4)^2)
= sqrt( 81 + 16)
=sqrt(97)
A sample of restaurants in a city showed that the average cost of a glass of iced tea is $1.25 with a standard deviation of 7¢. If a new restaurant charges a price for iced tea that has a z-value of -1.25, then what is the tea’s actual cost?
Answer:
The tea's actual cost is $116.25
Step-by-step explanation:
* Lets revise how to find the z-score
- The rule the z-score is z = (x - μ)/σ , where
# x is the score
# μ is the mean
# σ is the standard deviation
* Lets solve the problem
- The average cost of a glass of iced tea is $1.25
- The standard deviation of it is 7 cents
- A new restaurant charges a price for iced tea that has a
z-value of -1.25
* Lets change the average cost to cent
∵ $1 = 100 cents
∴ The average cost of a glass of iced tea = 1.25 × 100 = 125 cents
∵ z = (x - μ)/σ
∵ z = -1.25
∵ μ = 125
∵ σ = 7
∴ -1.25 = (x - 125)/7 ⇒ multiply both sides by 7
∴ -8.75 = x - 125 ⇒ add 125 to both sides
∴ 116.25 = x
* The tea's actual cost is $116.25
Answer: It is actually 1.16$ (The guy below accidentally added an extra 1)
Step-by-step explanation:
If two angles are complementary, they are complements of each other.
True or False
Graph the data in the table below. Which kind of function best
models the data? Write an equation to model the data. Please help ASAP
Answer:
C
Step-by-step explanation:
Try to plug in the first pair of numbers to eliminate some equations, all but C fail to satisfy the equation. So C is the answer.
Answer:
CStep-by-step explanation:
Notice that the table doesn't have an exponential behaviour. Because an exponential function has the point (0,1), because all powers with a null exponent are equal to 1.
Also, notice that the table doesn't show a linear relation, because y-variable has all values positive.
Therefore, the only relation that follows the values of the table is
[tex]y=2.5x^{2}[/tex]
Let's evalue each x-value
[tex]y=2.5(-2)^{2} =2.5(4)=10\\y=2.5(-1)^{2}=2.5(1)=2.5\\ y=2.5(0)^{2}=2.5(0)=0\\y=2.5(1)^{2}=2.5\\y=2.5(2)^{2}=10[/tex]
Therefore, the right answer is C. The given values show a quadratic relation.
A faster way to deduct the quadratic pattern is observing that y-values are symmetric no matter if x-values are positive or negative, that meanst he function is pair, or quadratic.
Please help, I am just so bad at this specific subject. I cannot get the hang of it, it's just so trippy to me.
Answer:
142°
Step-by-step explanation:
The angles of 38° and m<7 both make supplementary angles which equal to 180. Subtract 180 by 38.
Answer:
142
Step-by-step explanation:
Line M is a straight line. All straight lines have an angle measurement of 180 degrees.
m<7 + 38 = 180 Subtract 38 from both sides.
m<7 + 38 - 38 = 180 - 38
m<7 = 142
You roll a 6-sided die with faces numbered 1 through 6, and toss a coin. What is the probability of rolling a 2 or getting heads
P(2 or H) = P(2) + P(H) - P(2 and H)
What is the probability of getting a 2 P(2)? = 1/6
What is the probability of getting heads P(H)? = 1/2
P(2 and H) is the product of those two events since the events are independent. = 1/6 * 1/2 = 1/12
P(2 or H) = P(2) + P(H) - P(2 and H)
P(2 or H) = 1/6 + 1/2 - 1/12 = 7/12
What is the value of b?
Both chords are the same distance from the center of the circle ( the 12 inch lines are the same length).
This means that both chords are the same length. The bottom chord has a dimension of 22.5.
B id half the top chord so would be equal to half of 22.5
b = 22.5 / 2 = 11.25
Sully earns $80 by selling a laptop and $60 by selling a smartphone. He wants to make a profit of at least $6,800. Write an inequality to model the amount Sully earns by selling laptops and smartphones.
Answer:
The inequality that represent the problem is [tex]80x+60y \geq 6,800[/tex]
The solution in the attached figure
Step-by-step explanation:
Let
x ----> the number of laptops sold
y ----> the number of smartphones sold
we know that
The inequality that represent the problem is equal to
[tex]80x+60y \geq 6,800[/tex]
The solution of the inequality is the shaded area
Remember that the number of laptops or the number of smartphones must be a whole positive number
The graph in the attached figure
Answer:
the 2nd one isss x+y< 100
Step-by-step explanation:
Is cos theta=cos(-theta)
Answer:
TRUE
Step-by-step explanation:
An even function is a function that satisfies that f(x) = f(-x). Also, we know that cosine is an even function, therefore cos(theta) equals cos(-theta).
the quote for usd/jpy is listed as 119.68/75 as shown. how many japanese yes does it cost to buy 1 U.S. dollar?
the quote for usd/jpy is listed as 119.68/75 as shown. how many japanese yes does it cost to buy 1 U.S. dollar?
Answer:
the correct answer is 119.75
Answer:
the guy above is right
Step-by-step explanation: i took the test and it was
HELP!!!!!!!!
Which expressions are equivalent to -7+3(-4e-3)?
Choose all answers that apply:
(Choice A)
-4(3e+4)
(Choice B)
12e
(Choice C)
None of the above
ANSWER
(Choice A)
-4(3e+4)
EXPLANATION
The given expression is
[tex] - 7 + 3( - 4e - 3)[/tex]
We expand to get:
[tex] - 7 - 12e - 9[/tex]
We regroup the terms to get:
[tex] - 12e - 9 - 7[/tex]
Simplify now to get:
[tex] - 12e - 16[/tex]
We now factor -4 to obtain:
[tex] - 4(3e + 4)[/tex]
The correct choice is A.
The expression simplifies to -16 - 12e. None of the given choices match this expression. Therefore, the correct answer is (C) None of the above.
To determine which expressions are equivalent to -7+3(-4e-3), let's simplify the given expression step-by-step:
Start by distributing the 3:
-7 + 3(-4e - 3) = -7 + (3 * -4e) + (3 * -3)
= -7 - 12e - 9
Now, combine the constants:
-7 - 12e - 9 = -16 - 12e
None of the provided choices are equivalent to -16 - 12e:
Choice A: -4(3e + 4) simplifies to -12e - 16, which is close but not equivalent.Choice B: 12e is not equivalent to -16 - 12e.Choice C: None of the above is the correct answer.What is the remainder when 3x^4 +2x^3-x^2+2x-24)/(x+2)
Answer:
remainder = 0
Step-by-step explanation:
Using the Remainder Theorem
Given f(x) divided by (x + h) then the remainder is found by evaluating f(- h)
Here the divisor is (x + 2), hence evaluate at h = - 2
Let f(x) = 3[tex]x^{4}[/tex] + 2x³ - x² + 2x - 24, then
f(- 2) = 3[tex](-2)^{4}[/tex] + 2(- 2)³ - (- 2)² + 2(- 2) - 24
= 3(16) + 2(- 8) - 4 - 4 - 24
= 48 - 16 - 4 - 4 - 24 = 0 ← Remainder
Remainder = 0 , hence (x + 2) is a factor of f(x)
What’s the answer to this problem? (Photo included) thanks!
Answer:
C
Step-by-step explanation:
85+92+78+93=348
348/4=87
Answer:
.the answer is 93
Step-by-step explanation:
85 + 92 + 78 + 93= 348
348/4= 87 average
lim-0
(1 + 3x)/x =?????
Answer:
not existStep-by-step explanation:
[tex]\lim\limits_{x\to0}\dfrac{1+3x}{x}\\\\\lim\limits_{x\to0^+}\dfrac{1+3x}{x}=\dfrac{1+(3)(0)}{(+)}=\dfrac{1}{(+)}=+\infty\\\\\lim\limits_{x\to0^-}\dfrac{1+3x}{x}=\dfrac{1+(3)(0)}{(-)}=\dfrac{1}{(-)}=-\infty[/tex]
Answer:
See below.
Step-by-step explanation:
The two sided limit does not exist.
As x approaches 0 from negative values the limit is -∞.
As x approaches 0 from positive values the limit is ∞.